A study of anti-plaque efficacy and taste perception of Calendula officinalis mouth rinse - Arief, Erry Mochamad; Abidin, Zaridah Zainal; Sitheeque, Mohaideen; Mohamad, Md Azman PKM Seeni (Padjadjaran Journal of Dentistry, 2020)
Introduction: An ideal mouth rinse must have an acceptable taste and very efficient antiplaque activity. Herbal mouth rinse (Plandula®), containing extracts of Calendula officinalis and other specified herbs, is widely cultivated as a herb. It is a remarkable healing agent and even useful to act as homeopathic remedies. Previous studies have compared this product with placebo; however, comparison against chlorhexidine have not been conducted thus far. Aim of this research was to analyse the efficacy of Calendula in Plandula® for controlling dental plaque and the acceptability of its taste in comparison with chlorhexidine. Methods: A double-blind, 3-day plaque regrowth, crossover, clinical study was conducted towards 16 volunteers participated in two periods, three days each, with modified oral hygiene practices through an intervening washout period of 4 days. At the commencement of each period, the participants received oral prophylaxis. They used the allocated mouth rinse and brushed teeth without toothpaste in all of the tooth surfaces, except palatal and lingual over three days. On the fourth day, the subjects were returned for plaque index measurement only on the palatal and lingual surfaces by the Quigley Hein index (modified by Turesky). The participants rinsed with 10 ml of allocated mouth rinse three times daily for 30 seconds after tooth brushing. The participants followed the same steps during the second period using the alternate mouth rinse. They were also asked to taste both mouth rinses and evaluate with a Visual Analogue Scale (VAS).Results: Median plaque score for Plandula® mouth rinse was slightly higher compared to chlorhexidine but not statistically significant, with the p-value=0.636 (p>0.05). The mean VAS scale score for Plandula® taste perception was lower than the chlorhexidine, and statistically significant (p-value=0.01; p<0.05). Conclusion: Plandula® mouth rinse that contain calendula officinalis comparable with chlorhexidine in controlling dental plaque accumulation, with an acceptable taste.